Research on the Experiment Analysis of Spontaneous Combustion Characteristics of the15# Coal Seam in Fusheng Coal Mine - Hao, Yu (International Journal of Natural Resources and Environmental Studies, 2024)
According to the spontaneous combustion characteristics of 15# coal seam in the fusheng mine, the programming temperature rising test with the coal sample from fusheng coal mine was conducted, which researched the concerntration and the corresponding pyrolysis termperature of index gas during programming temperature rising of the coal sample. The index gases included the CO, CO2, CH4, C2H4, C2H2 and so on.